Pendampingan Pembuatan Penyanitasi Tangan Spray di PAKYM Surakarta - Erawati, Emi; Nurwaini, Setyo; Wijayanti, Rita; Permata, Almira; Naufal, Muhammad Raihan; Falakhuddin, Muhammad; Wardhana, Krisna Wisnu; Setiawan, Panji Rasma (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Community service was done on 12nd March 2022 in Muhammadiyah Orphanage Hall, Surakarta, Central Java. The community service was followed by Vocational High School student who stay in Muhammadiyah Orphanage Hall as much as 9 students. The nine students were who followed students from 3 vocational high school namely SMK Negeri 5 Surakarta, SMK Muhammadiyah 3 Surakarta, and SMK Muhammadiyah Kartasura. The nine students were majored electrical, automotive and electrical engineering. The aim of community services for giving knowledge not only theory but also practice in making spray hand sanitizer on the other hand spray hand sanitizer was made pass the germ test namely Escherichia Coli bacteria. The community services were divided by 3 steps namely science and technology diffusion, public education, and making hand sanitizer.